Scalable data replication in content-centric networking based on alias names. (January 2015) - Garcia-Reinoso, Jaime; Fernández, Norberto; Vidal, Ivan; Arias Fisteus, Jesús
Abstract: Content-Centric Networking (CCN) is a clean-slate proposal to redesign the current Internet by focusing on the content itself, instead of the classical computer-to-computer communication. In this paper we address scalability issues of the Forwarding Information Base (FIB) in CCN. Our solution proposes both the use of hierarchical names assigned by access providers and a novel alias name architecture. With the former, we allow the aggregation of entries at the routing tables of CCN content routers, while the latter reduces the processing load at those routers when replicas exist in different parts of the network. With some minor changes to the original proposal, we provide a scalable solution for data replication in CCN, which inherently supports content mobility at the same time. We validate our scheme by (1) comparing the scalability of CCN against our proposal and by (2) implementing and testing a proof-of-concept software based on CCNx, to prove the viability of this approach.